2022
DOI: 10.1007/s00167-021-06836-w
|View full text |Cite
|
Sign up to set email alerts
|

Increased inflammatory response is associated with less favorable functional results 5 years after total knee arthroplasty

Abstract: Purpose Allergy against implant materials is discussed controversially and still not fully understood. Despite these controversies, a relevant number of patients receive hypoallergenic knee implants. The aim of this study was to compare a new coating system with the standard implant in total knee arthroplasty (TKA). Additionally, the influence of proinflammatory cytokines on patient-reported outcome measures (PROMs) was investigated. Methods 120 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Furthermore, this low-level in ammation persists postoperatively and affects the outcomes of TKA. This is consistent with a study by Jörg Lützner et al, which found that patients with an increased in ammatory response have poorer functional outcomes [31]. In the imaging evaluation, the JLCA is considered to re ect medial compartment narrowing due to cartilage wear and laxity of the knee ligaments.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, this low-level in ammation persists postoperatively and affects the outcomes of TKA. This is consistent with a study by Jörg Lützner et al, which found that patients with an increased in ammatory response have poorer functional outcomes [31]. In the imaging evaluation, the JLCA is considered to re ect medial compartment narrowing due to cartilage wear and laxity of the knee ligaments.…”
Section: Discussionsupporting
confidence: 85%
“…Several proinflammatory cytokines have been reported to play a role in healing and pain after TKA [29,30]. It has been demonstrated that an increased inflammatory reaction after TKA results in less favorable results [31] and that cytokines were lower after being coated compared to standard TKA [32]. Surface modification of TKA may therefore result in less inflammation and better results.…”
Section: Hypersensitivity and Immunological Reactionsmentioning
confidence: 99%